Independensi Lembaga Kejaksaan Perspektif Filsafat Hukum - Lilik Dwy Prasetio (Laskar Karya, 2024)
One of the fundamental principles in the justice system is the independence of the prosecutor's office, which guarantees that the prosecutor's office can carry out and complete its duties and authorities without any pressure or intervention from other parties. This research aims to examine and analyse the independence of the prosecutor's office in the perspective of legal philosophy. The method used in this research is normative juridical research method, with three main approaches, namely legislative approach, conceptual approach, and case approach, then analysed deductively based on relevant legal theories, concepts, and doctrines. The results showed that the independence of the prosecutor's office in the perspective of legal philosophy stated that the prosecutor's office must be able to carry out its duties and authorities based on the principles of universal justice derived from moral and ethical values. In other words, the independence of the AGO must be orientated towards substantive justice, not just formal justice.